1996
DOI: 10.1111/j.1476-5381.1996.tb15312.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐activity relationships of new agonists and antagonists of different metabotropic glutamate receptor subtypes

Abstract: 1 We investigated the agonist and antagonist activities of 22 new phenylglycine and phenylalanine derivatives for metabotropic glutamate receptors (mGluRs) by examining their effects on the signal transduction of mGluR1, mGluR2 and mGluR6 subtypes expressed in Chinese hamster ovary cells. This analysis revealed several structural characteristics that govern receptor subtype specificity of the agonist and antagonist activities of phenylglycine derivatives.2 Hydroxyphenylglycine derivatives possessed either an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 37 publications
(62 reference statements)
5
48
0
Order By: Relevance
“…The stronger the tetanization, the less potent were the mGluR antagonists MCPG and 4-CPG in affecting the time course of the resulting potentiation. MCPG has been characterized as a competitive antagonist of class I and class II mGluRs, whereas 4-CPG displays a selectivity toward class I mGluRs and only weak activity on mGluRs of class II (Davies et al, 1995;Sekiyama et al, 1996). Because in most of our experiments the results obtained with the two antagonists were very similar, the effects of these compounds on LTP may be assigned to an action on class I mGluRs.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The stronger the tetanization, the less potent were the mGluR antagonists MCPG and 4-CPG in affecting the time course of the resulting potentiation. MCPG has been characterized as a competitive antagonist of class I and class II mGluRs, whereas 4-CPG displays a selectivity toward class I mGluRs and only weak activity on mGluRs of class II (Davies et al, 1995;Sekiyama et al, 1996). Because in most of our experiments the results obtained with the two antagonists were very similar, the effects of these compounds on LTP may be assigned to an action on class I mGluRs.…”
Section: Discussionmentioning
confidence: 66%
“…somewhat lower affinity at mGluRs of class II (Davies et al, 1995;Sekiyama et al, 1996), we repeated the same experiments with 4-CPG, which represents in the employed concentration range a specific antagonist toward class I mGluRs. 4-C PG (100 M) had no effect on the initial potentiation (4-C PG group: 208 Ϯ 9%, n ϭ 7; control: 206 Ϯ 10%, n ϭ 7) and the maintenance of LTP (240 min after tetanus: 135 Ϯ 8% and 132 Ϯ 6%, respectively) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that this effect is blocked by infusion of the cystine-glutamate exchange inhibitor CPG into the nucleus accumbens. Because CPG also acts at metabotropic glutamate receptors, we selected a concentration (500 nM) that is significantly lower than the EC50s of CPG to block group I mGluRs (40-65 µM) or stimulate group II mGluRs (570-970 µM) (Cavanni et al, 1994;Thomsen et al, 1994;Sekiyama et al, 1996). As a result, the present findings indicate that N-acetylcysteine blocks cocaine-induced reinstatement of drug seeking by targeting cystine-glutamate exchange by system x c -in the nucleus accumbens.…”
Section: N-acetylcysteine Blunts Cocaine-induced Reinstatement By Tarmentioning
confidence: 92%
“…Within these limitations, the receptors seemed to have no effect on the neurotoxicity of L-b -ODAP in rat primary cortical neurons. Although MCPG acts on both group I and group II mGluRs as an antagonist, 29) the fact that MCPG was almost as effective as AIDA also excludes the possibility that group II mGluRs are involved in the neurotoxicity of L-b -ODAP.…”
Section: Effect Of L-b B-odap On Glutamate Transporters Expressed Inmentioning
confidence: 99%